The Medusa Gaze in Contemporary Women's Fiction : Petrifying, Maternal and Redemptive. - Alban, Gillian M. E. (Cambridge Scholars Publishing, 2017)
This book offers striking insights into the desires and frustrations of women through the narratives of impressive contemporary novelists. Crafting its analysis on the gaze as presented by Lacan and Sartre, the book demonstrates how the subject creates her own ego against her alter egos or hostile others in the mirrors facing her, offering insight into women's powers and weaknesses. The first two mirroring chapters trace the women stalking its pages under a panoptic gaze, as they learn how to revert their look defiantly back onto others. Some win assurance through their own assertive gaze; oth.